Be My Slave; The Main Character's Libido In Sendalu Novel By Chavchay Syaifullah - Nurlailatul Qadriani; Ramadoni Ramadoni; Nur Israfyan Sofian; Zahrani Zahrani (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
The objective of the study is to describe the main character's libido problem in Sendalu Novel by Chavchay Syaifullah used Sigmund freud's psychoanalytic theory. Which is explaining the sexuality that appears in the novel with used id, ego and superego. The focus of this research is how the psychological factors work. The result of the research showed that there are two factors that causes the main character's libido problem. First is the external factors and the second is the internal factors. The external factors are family environment and social environment. While the internal factors are the psychological factors. Basically, these two factors are interplay, but at first, the superego dominated the behavior of the main character. However, after individual obtained negative influence from his parent continuously, then the superego became week. Therefore, the id of the main character became stronger. Until ego tends to do all the id's desire in the form of libido. Superego again dominated the main character because there is an anxiety drive that presses individual. At first, the anxiety came from outside of the main character's self and then became part of the main character's self.